Sobre o desempenho ocupacional, as atividades da vida diária, as atividades instrumentais de vida diária e as ocupações em uma unidade de atendimento à pessoa idosa - SARMENTO, Mara Daniele de Sousa (2023)
Introduction: With increasing life expectancy, the aging process became more evident, and as a result, the reflections on the subject increased. The occupation, which results from choice, motivation and meaning within a context of support and environment, directly influence the quality of this aging. As a result of these reflections, a new look emerges for the Institutions of Long Stay for the Elderly. In this context, it is common for the elderly person to lose their autonomy, and to become passive to the environment. Objective: To evaluate occupational performance, activities of daily living, instrumental activities of daily living and occupations of the elderly in an Elderly Care Unit. Method: This is a qualitative and quantitative study, which will be carried out with institutionalized older people aged over 6 months, in an Elderly Care Unit, which will be evaluated, based on a structured questionnaire, field diary and four protocols (MMSE), the Canadian Measurement of Occupational Performance (COPM), the Katz Index and the Lawton and Brody Scale. Results and discussion: The study was carried out with 07 elderly people, with low schooling and income up to a minimum wage. This population made possible satisfactory experiences, since most were Independent in Daily Life Activity, Partial Independent in Instrumental Activity of Daily Life, obtaining an Occupational Performance in which the biggest problem was the loss of productive activities. This information is consistent with the reports about occupations performed before and after the institutionalization process. Final considerations: The research presented results that contribute to studies concerning the practice of actions within institutions that shelter elderly people in social vulnerability, as well as arouse the interest and disposition of scientific research articulating the interest of research on the occupational dimension.